The Prevalence of Back and Leg Pain and the Cross-sectional Association With Adverse Health Outcomes in Community Dwelling Older Adults in England. Issue 1 (1st January 2021) - Williamson, Esther; Sanchez Santos, Maria T.; Morris, Alana; Garrett, Angela; Conway, Oliver; Boniface, Graham; Fairbank, Jeremy; Lamb, Sarah E.
Abstract : Study Design: Cross-sectional analysis of the Oxford Pain, Activity and Lifestyle (OPAL) Cohort Study. Objective: The aim of this study was to assess the prevalence of back pain (BP) and leg pain and determine their relationship with adverse health states among older adults in England. Summary of Background Data: Epidemiological data describing the prevalence of BP and leg pain in older adults in England is lacking. Methods: A total of 5304 community-dwelling adults (aged 65–100 years) enrolled in the OPAL cohort study who provided data on BP and leg pain were included. Participants were classified into four groups based on reports of back and leg pain: no BP, BP only, BP and leg pain which was likely to be neurogenic claudication (NC), and BP and leg pain which was not NC. Adverse health states were frailty, falls, mobility decline, low walking confidence, poor sleep quality, and urinary incontinence. We collected demographic and socioeconomic information, health-related quality of life, and existing health conditions, and estimated the association between BP presentations and adverse health states using regression analysis. Results: Thirty-four percent of participants (1786/5304) reported BP only, 11.2% (n = 594/5304) reported BP and NC and 8.3% (n = 441/5304) reported BP and non-NC leg pain. Participants with BP had worse quality of life compared to those without BP. All BP presentations were significantly associated with adverse health states. Those with NC were most affected. In particular, there was greater relative risk (RR) of low walking confidence (RR 3.11, 95% confidence interval [CI] 2.56–3.78), frailty (RR 1.88, 95% CI 1.67–2.11), and mobility decline (RR 1.74, 95% CI 1.54–1.97) compared to no BP. Conclusion: Back and leg pain is a common problem for older adults and associated with reduced quality of life and adverse health states. Findings suggest a need to develop more effective treatment for older adults with BP especially for those with neurogenic claudication. Level of Evidence: 2 Abstract : Supplemental Digital Content is available in the textThis study investigated the prevalence of back and leg pain in older adults and the association with adverse health states including frailty, falls and immobility. The report of back and leg pain was associated with adverse health states. The associations were strongest in participants reporting neurogenic claudication.